New Methods to determine the come-off time of paper labels - Wenk, Georg; Weber, Ingrid; Pahl, Roland (BrewingScience, 2010)
In the beverage industry labels are removed from returnable bottles in bottle cleaning machines. For a successful cleaning process the labels come-off time is crucial. If the labels detach too late in this process, they can block rinsing nozzles and affect the cleaning effectiveness of the machine.The term "come-off time" is defined by DIN 16524-6 as the time a tested label needs, to fully separate from a Petri dish when immersed in a caustic bath. However, the method according to DIN 165246 does not account for any double bonding of neck-ring labels, used on so called long-neck or ale bottles. Furthermore, many procedure steps of DIN 16524-6 are executed manually by the examiner, are not defined precisely or are impractical. Tests performed at the VLB Berlin showed that results between different examiners can differ significantly.In this paper the results of the IGF research project 15343 N are presented. Within this project the come-off behaviour of different paper labels was tested against various influencing factors. It was found that the amount of labelling glue is of particular importance in combination with metallised paper labels. Deriving from that knowledge, an existing model for the come-off behaviour was extended, allowing to develop a Modified Method and an Extended Method to overcome existing limitations and inaccuracies of DIN 16524-6.